Hypophysitis During Immune Checkpoint Inhibitor Therapy: Epidemiology, Clinical Manifestations and Treatment Considerations - Grabowska, Julia; Jędrysiak, Joanna; Kolanko, Magdalena; Kolasa, Wiktoria; Korzeniowska, Anna; Kosidło, Patrycja; Lelonkiewicz, Martyna; Mikółka, Karolina; Szeliga, Katarzyna; Stołecka, Greta (Journal of Education, Health and Sport, 2026)
Background. Immune checkpoint inhibitors (ICIs) have substantially improved outcomes in modern oncology; however, their increasing use is associated with immune-related adverse events, including endocrine complications. Among them, ICI-induced hypophysitis represents a clinically important condition that may result in hypopituitarism and potentially life-threatening hormonal deficiencies. Aim. This narrative review summarizes current evidence regarding the epidemiology, pathophysiology, clinical presentation, diagnostic approach, and management of ICI-induced hypophysitis. Material and methods. A structured PubMed search was conducted between March and April 2026. Studies published within the last 10 years evaluating hypophysitis, hypopituitarism, or pituitary insufficiency associated with ICI therapy in humans were included. Additional cohort studies and clinical trials reporting incidence data were analyzed descriptively. Results. Eleven studies involving 8,310 patients were included in the epidemiological analysis. The incidence of grade ≥3 hypophysitis ranged from 0-6% with PD-1 inhibitors, reached up to 13.6% with ipilimumab, and ranged from 1.9-19.1% with combination therapy. Earlier onset was observed in CTLA-4-based regimens, whereas PD-1 inhibitor-associated hypophysitis tended to occur later during treatment. Clinical manifestations are frequently nonspecific, which may delay diagnosis and increase the risk of clinically significant adrenal insufficiency. Conclusions. ICI-induced hypophysitis is a clinically significant endocrine adverse event whose incidence and timing depend on the therapeutic regimen used. Because symptoms are often subtle and nonspecific, early recognition requires increased clinical awareness supported by hormonal evaluation and imaging studies. Prompt diagnosis and appropriate hormone replacement therapy are essential to reduce complications and improve patient outcomes.